Public participation in development – the idea of a development 'jury' servic - Howsam, Peter; Quinn, J. (Lawtext Publishing, 2005)
Delivering sustainable development requires consideration of social, economic and environmental factors. Many players are involved but in all cases at some point society (the general public) need to have a say. To facilitate this, we need something which we don’t have at present, i.e. a fair, representative, effective, efficient and affordable system to allow public participation in decision makin